PENGARUH PEMAHAMAN AKUNTANSI, INSENTIF PAJAK DAN PREFERENSI RESIKO PAJAK TERHADAPKEPATUHAN WAJIB PAJAK DENGAN PERSEPSI WAJIB PAJAK SEBAGAI VARIABEL MODERASI (Survei Kasus pada UMKM Kecamatan Nogosari, Boyolali ) - Sukmadewi, Anissya (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
This study to examine the effect of accounting understanding, tax incentives, and risk preference on MSME taxpayer compliance with risk preference as a moderating variable. This research was conducted on 1,035 MSME in Nogosari District, Boyolali, the type of data used is quantitative data. The data sources used are primary and secondary data. The entire population in this study were all MSMEs in Nogosari District. The sample used in this study were MSMEs in each village in Nogosari District, including 12 Bendo Villages, 6 Glonggong Villages, 3 Guli Villages, 7 Jeron Villages, 6 Kenteng Villages, 3 Ketitang Villages, 10 Keyongan Villages, 10 Pojok Villages, 6 Potronayan Village, 4 Pulutan Villages,8 Rembun Villages, 9 Sembungan Villages, and 7 Tegalgiri Villages. The sampling technique used was cluster random sampling method. This study shows that accounting understanding, tax incentives, and risk preferences have a significant effect on the level of compliance of MSME taxpayers. The results of the regression test in this study indicate that the perception of taxpayers moderates by strengthening the variables of accounting understanding, tax incentives, and risk preferences in MSME taxpayer compliance.